Filosofi Kaliring dalam Upacara Wara di Kabupaten Barito Selatan - Handoko Handoko; I Wayan Salendra; Ni Putu Sri Pinatih; Anak Agung Gede Wiranata (Jurnal Penelitian Agama Hindu, 2026)
Kaliring is a sacred structure used in the Wara death ceremony among the Hindu Kaharingan community in South Barito Regency, Central Kalimantan. This tradition serves a dual purpose: physically as a container for ancestral skulls and symbolically as a representation of the relationship between humans and ancestral spirits. However, modernization, lifestyle changes, and the lack of academic documentation have led to a gradual decline in its preservation and meaning. This study aims to describe the physical form of Kaliring, identify the symbols contained within it, and analyze the cultural and religious values reflected in the context of the Wara ceremony. The research employs a qualitative approach with a naturalistic method. Data were collected through participant observation, in-depth interviews with religious and customary leaders, and documentation studies of artifacts and ritual records. The findings reveal that Kaliring is made of ironwood in a rectangular shape supported by two pillars and decorated with motifs of animals, plants, human figures, and red cloth symbolizing purity and spiritual strength. These symbols embody educational (religious, social, ethical, and character), cultural, and economic values that reflect the belief system and social order of the Dayak Kaharingan people. The culmination of the Wara ceremony is marked by the purification of skulls by the Kandung (holy person), followed by their placement into the Kaliring as a symbol of the ancestral spirit’s (liau) transformation into a deity (kalilungan). The study concludes that Kaliring is a sacred cultural heritage that reinforces spiritual identity and preserves the continuity of local wisdom within the Hindu Kaharingan community.